Volume 2C: Turbomachinery 2015
DOI: 10.1115/gt2015-42832
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Compressor Variable Geometry Settings Using Multi-Fidelity Simulation

Abstract: Variable geometry blade rows are a common instrument to avoid compressor instabilities which occur especially at low- and full-speed operation of gas turbines. The operating settings of variable stator vanes (VSVs) are typically obtained from expensive and time consuming performance rig tests and are not known during the early design phase of a gas turbine. During preliminary design of the overall engine it is common practice to use default component characteristics based on considerable enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For example, Kim et al (2015), who also coupled a mean-line tool with a performance tool, showed that the settings for variable guide vanes (VGVs) can only be set meaningfully related to engine overall performance. Using a 2-D through flow tool, Reitenbach et al (2015) had also confirmed this.…”
Section: Coupled Model Simulationmentioning
confidence: 71%
“…For example, Kim et al (2015), who also coupled a mean-line tool with a performance tool, showed that the settings for variable guide vanes (VGVs) can only be set meaningfully related to engine overall performance. Using a 2-D through flow tool, Reitenbach et al (2015) had also confirmed this.…”
Section: Coupled Model Simulationmentioning
confidence: 71%
“…The advantages of the application of a central data model as infrastructure for the exchange of data during multi-fidelity simulation were demonstrated in Refs. [21][22][23].…”
Section: Data Modelingmentioning
confidence: 99%
“…28 Reltenbach (2015) used a 2D method to analyze meridional flow field and give the optimized variable stator vanes setting for the minimum thrust specific fuel consumption and maximum surge margin. 29 Empirical models in the dimensional reduction models of turbomachinery have been developed for a long time. But to provide reliable support to match multistage compressors, the level of model accuracy should be quite high.…”
Section: Introductionmentioning
confidence: 99%